Agama dan Aktualisasi Diri dalam Perspektif Filsafat Muhammad Iqbal (1873-1938) - Lidinillah, Mustofa Anshori (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2000)
There are two opinions that are extremely different ahout religion function to self-actualization process. Firstly, religion is needed in self-actualization process. Secondly, religion inhibits self-actualization process. The research will make a clearance of that problem and to discover a conception about religion which are conducive to the self-actualization effort.Material object of the research isÂ· Iqbal 's conception about religion and self, and the formal object is religion philosophy. Hermeneutic method is used in this research. There are some procedures of method, namely interpretation, analysis synthesis, coherency, comparation, and heuristics.The result ofresearch are: the self is more potensia than actus. Potensia will become actus through out s lf-actualization process, and will final at insan kamil. lnsan kamil is the human like God, a human ideal condition. Religion norms are the one ofrepresentative self-actualization procedures. Religion can be called modus of existence. Proportional understanding about religion is needed for its. The understanding which placed the human as the central ofthe world, but the spiritual consciousness which oriented to God is growth in his self That understanding called anthropocentric-spiritualistic conception. Iqbal's conception about religion is anthropocentric-spiritualistic one. Self of human became central subject in his philosophy, and whole of his philosophy systems are formatted by the religion. Iqbal's conception about religion can be a reference in self- actualization.